2014
DOI: 10.2298/jas1402117c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decaying leaf litter and inorganic fertilizer on growth and development of maize (Zea mays L.)

Abstract: The effects of decaying leaf litter of Tithonia diversifolia and Vernonia amygdalina as organic fertilizer, inorganic fertilizer and their combination effects on the growth and development of maize were studied in a screen house. Twenty-four experimental bags filled with 20 kg of loamy soil were laid out in a completely randomized design with six treatments and four replications for each treatment which included: 250 g of decaying leaves of T. diversifolia as mulch (T 1 ), 250 g of decaying leaves of V. amygd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…From this result it was found that plant dry weight decreased significantly with the increase of industrial effluent. Chukwuka et al, (2014) affected maize plant dry weight which was dissimilar with this stage also.…”
Section: Flowering Stagementioning
confidence: 83%
See 3 more Smart Citations
“…From this result it was found that plant dry weight decreased significantly with the increase of industrial effluent. Chukwuka et al, (2014) affected maize plant dry weight which was dissimilar with this stage also.…”
Section: Flowering Stagementioning
confidence: 83%
“…Root length and maize plant dry weight were significantly (P<0.05) higher for fresh water irrigation treatment (T1) compared to industrial effluent irrigation treatments. Umebese and Onasanya (2007) and Chukwuka et al, (2014) stated that increasing concentration of industrial effluents gives rise to gradual increase in the root length and maize plant dry weight, however, this finding is fully disagreed with those findings. Grigorou et al (1987) also reported that using of sewage water for irrigation improved root length.…”
Section: Maturity Stagementioning
confidence: 86%
See 2 more Smart Citations
“…Maize production in Nigeria and in sub-Saharan Africa has been found to have an increasing trend of between 2% and 3% annually (Boxall, 2000). It is one of the important staple and consumed food crops in sub-Saharan Africa (Chukwuka et al, 2014). Maize also known as corn is a crop that is cultivated widely throughout the world in a range of agro-ecological environments (IITA, 2009).…”
Section: Introductionmentioning
confidence: 99%